Trends and Developments in Carbon Accounting Research Over a Decade: a Bibliometric Analysis - Rita Rosalina; Muhammad Ja'far Shodiq (Library of Sultan Agung Islamic University, 2026)
This study aims to analyze trends and developments in carbon accounting research during the 2016–2026 period through a bibliometric approach. Research data were obtained from the Scopus database using keywords related to carbon accounting. The article selection process was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, resulting in 1,197 articles meeting the criteria for analysis. Bibliometric analysis was performed in RStudio using the Biblioshiny package. The results show that publications on carbon accounting have increased significantly over the past decade, with an average annual growth rate of 10.33%. China has the highest number of publications, followed by the United States, Australia, the United Kingdom, and Germany. Keyword analysis shows that research themes are dominated by issues of carbon dioxide, carbon emissions, climate change, greenhouse gases, and sustainable development. Keyword network analysis identified three main clusters: carbon emission measurement and reporting, emission control and energy efficiency, and climate change and life cycle assessment. These results demonstrate that carbon accounting research has evolved from a focus on measuring and reporting emissions to a more strategic approach that supports sustainability management, climate change mitigation, and the transition to a low-carbon economy. This research provides a comprehensive understanding of the intellectual structure, directions for development, and future research opportunities in carbon accounting, particularly those related to ESG, net-zero emissions, and sustainability reporting.